กฎหมายเลือกตั้ง: ศึกษากรณีการควบคุมการปิดประกาศและติดแผ่นป้ายโฆษณาหาเสียงเลือกตั้ง - ธันยพร จันทร์เปีย (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This thesis aims to study the laws relating to controls on posters and signs in respect of an election. All relating laws, such as, the Constitution of Thailand, relating Acts, regulations and the Election Commission’s notifications have been analyzed to justify possible ways which will help to implement the laws more effectively. The study has shown some problems :1) a problem where a candidate in an election does not remove an election sign or poster posted outside a polling station though an advertisement for election is prohibited by law from 6.00 p.m. on the eve of the polling day until the election period ends; 2) a problem concerns criteria on prohibition of an election poster and sign posting in public places; 3) suitability of provisions set out in the Organic Act on the Election of Members of the House of Representatives and the Installation of Senators, B.E. 2550 (2007) which prohibit the posting of an election sign or poster in private premises while the same is allowed under the Election of Local Councils Members or Local Administrators Act B.E. 2545 (2002) in case that the permission from an owner or possessor of the private premises is obtained ; and 4) a problem concerns determination of restrictions on an election sign and poster posting in regulations and notifications issued by the Election Commission.Therefore, to solve those unclear issues, it is recommended that: 1) there must be an additional rule in the Election Commission’s notices clearly indicating the distance between a polling station and where an election sign or poster can be posted, including clearly indicating that if an election sign or poster was posted legally before the restrictive time, it shall not be considered as contravening against the law; 2) there must be a rule indicating that the government should provide areas where an election sign and poster is allowed to be posted and a rule providing that an election sign and poster must not be posted in public roads, public places and other government agencies’ places; 3) the laws relating to a local election must be amended by prohibiting the post of an election sign and poster in the private property, similarly with the prohibition in a general election in both general and local level equally; and 4) the rule in the Election Commission’s notice must also be available in the Acts relating to an election, in order to impose a criminal offence for a contravention of law.